Hard times for tolerance? The hidden intolerance in the current financial bail-outs of European Union - Pereira Menaut, Antonio-Carlos; Martínez Arribas, Fernando (Derecho Público Iberoamericano, 2013)
This paper seeks to make, without systematizer character, a brief conceptualization of tolerance, then contextualize the present time, approaching its constitutional focus and the impact on the idea of tolerance, suppose the conditions governing bailouts in the European Union adopted on certain states (Greece, Ireland, Portugal, or with a different nature, Spain). This study links the idea of tolerance sustained in respect human dignity, that is, respect for the other’s identity although not share their positions. Notion that could apply to legal and constitutional perspective and facilitate the functioning of a regional model composed of various tates, as in the case of the European Union in the framework of multilevel governance. However, the authors explain the reasons why in the current context of the European Union (by reference to the terms of the bailouts) this idea of tolerance is not at its best stage.